TRANSCENDING JUSTICE: INTEGRATING RESTORATIVE PRINCIPLES WITH THE DIVINE VALUES OF PANCASILA - Farid, Achmad Miftah; Maulani, Indah; Fatihah, Nada Nabila; Lestari, Sri (Universitas Syiah Kuala, 2024)
This study investigates the integration of restorative justice principles with the divine values enshrined in Pancasila, the ideological and philosophical foundation of the Indonesian people. The spiritual and ethical dimensions of Pancasila can enrich and enhance restorative justice practices, providing a framework for a more religious and holistic approach to justice. Conducted using normative methods and a philosophical lens with a metaphysical dimension, this qualitative analysis examines the compatibility and potential synergy between these two paradigms, incorporating the transcendental aspects of Pancasila into criminal law enforcement. Furthermore, this study encourages readers to expand their understanding of justice beyond conventional paradigms, advocating for a more inclusive and transformative model. It suggests that law enforcers engage pious individuals and Indigenous leaders in handling criminal cases to ensure that the resolution processes remain unaffected and just.